2019
DOI: 10.7759/cureus.5293
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Duloxetine and Pregabalin in Pain Relief Associated with Diabetic Neuropathy

Abstract: Introduction Painful diabetic peripheral neuropathy (PDPN) complicates 25% of type II diabetes mellitus. It has a profound impact on diabetes-related morbidity and worsens the quality of life. Both pregabalin and duloxetine may be indicated for PDPN. In this study, the efficacy of duloxetine and pregabalin was compared in patients with PDPN. Methods It was a single-centre open-label study conducted with patients of diabetes mellitus type II diagnosed with PDPN. Patients were randomized to receive 60 mg/daily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In our study, DLX was more effective than PGB in reducing the neuropathic pain in diabetes; however, the difference was not statistically significant. Similar findings regarding the efficacy of DLX and PGB in diabetic peripheral neuropathic pain were reported by Shahid et al [ 16 ]. Goldstein and colleagues compared the dose-related efficacy of DLX for peripheral neuropathic pain.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, DLX was more effective than PGB in reducing the neuropathic pain in diabetes; however, the difference was not statistically significant. Similar findings regarding the efficacy of DLX and PGB in diabetic peripheral neuropathic pain were reported by Shahid et al [ 16 ]. Goldstein and colleagues compared the dose-related efficacy of DLX for peripheral neuropathic pain.…”
Section: Discussionsupporting
confidence: 89%
“…Synergistic inhibition of these neurotransmitters causes less transmission of pain signals from periphery to CNS. A number of preclinical and clinical trials have shown increased tolerance to pain with reduced pain symptoms in diabetic-induced painful neuropathy [ 125 127 ]. Pathogenic mechanism involving NF- κ B can cause spinal glial cells to secrete active substances and cytokines that can cause a sustained neuropathic pain.…”
Section: Fda-approved Drugsmentioning
confidence: 99%
“…For the management of painful diabetic neuropathy, pregabalin is a first line of treatment according to international guidelines. Dose-dependent studies have been conducted on pregabalin drug to quantify the pain intensity in diabetes-induced neuropathies [ 125 , 132 , 133 ]. Pain reduction was less than 50% in 3 : 10 patients taking 300/600 mg pregabalin daily as compared to 2 : 10 with placebo.…”
Section: Fda-approved Drugsmentioning
confidence: 99%
“…9 Pregabalin has been compared with duloxetine in previous trials. 10,11 A study done by Shahid et al 10 found statistically significant reduction in pain scores over time from baseline to 12 weeks (P < 0.001) with both duloxetine and pregabalin. Devi et al, 11 evaluated clinical efficacy of gabapentin, duloxetine, and pregabalin in PDN and revealed a significant reduction in Visual Analogue Scale (VAS) at the end of 12 weeks in all three groups (P < 0.05) but no significant difference between the groups.…”
Section: Introductionmentioning
confidence: 97%